2019
DOI: 10.1186/s40478-019-0728-0
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 reduces neuropathology in a mouse model of Alzheimer’s disease by remodeling peri-plaque astrocyte structure

Abstract: Redistribution of the water channel aquaporin-4 (AQP4) away from astrocyte endfeet and into parenchymal processes is a striking histological feature in mouse models of Alzheimer’s disease (AD) and other neurological conditions with prominent astrogliosis. AQP4 redistribution has been proposed to impair bulk Aβ clearance in AD, resulting in increased amyloid deposition in the brain; however, this finding is controversial. Here, we provide evidence in support of a different and novel role of AQP4 in AD. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 60 publications
(80 reference statements)
5
46
0
1
Order By: Relevance
“…An early study from our laboratory has reported that AQP4 deficiency decreases Aβ uptake in cultured astrocytes, and in turn attenuates changes in MAPK signaling pathways, finally reducing astrocyte activity [46]. Similarly, reduced reactive astroglosis is likewise 13 observed in 7-9-month-old AQP4 -/-/5xTg-AD mouse brains [47]. These data together indicate that long-term loss of AQP4 not only damages glymphatic clearance of Aβ, but also decreases astrocyte phagocytosis of Aβ, in turn exacerbating the pathological progression of AD.…”
Section: Discussionmentioning
confidence: 81%
“…An early study from our laboratory has reported that AQP4 deficiency decreases Aβ uptake in cultured astrocytes, and in turn attenuates changes in MAPK signaling pathways, finally reducing astrocyte activity [46]. Similarly, reduced reactive astroglosis is likewise 13 observed in 7-9-month-old AQP4 -/-/5xTg-AD mouse brains [47]. These data together indicate that long-term loss of AQP4 not only damages glymphatic clearance of Aβ, but also decreases astrocyte phagocytosis of Aβ, in turn exacerbating the pathological progression of AD.…”
Section: Discussionmentioning
confidence: 81%
“…An early study from our laboratory has reported that AQP4 deficiency decreases Aβ uptake in cultured astrocytes, and in turn attenuates changes in mitogen-activated protein kinase pathways, finally reducing astrocyte activity [48]. Similarly, reduced reactive astroglosis is likewise observed in 7-9-monthold AQP4 -/-/5xTg-AD mouse brains [49]. These data together indicate that long-term loss of AQP4 not only damages glymphatic clearance of Aβ, but also decreases astrocyte phagocytosis of Aβ, in turn exacerbating the pathological progression of AD.…”
Section: Discussionmentioning
confidence: 87%
“…Despite the fact that GFAP and thus astrogliosis can be considered a robust indicator of the disease, we failed to observe any significant overt change in the water channel AQP4, thought to be involved in the glymphatic clearance of Aβ [82,83] and proposed to be disrupted in AD [36]. Nevertheless, our measurements of AQP4 were either sampled at random within the temporal lobe via histology or represented total tissue levels in immunoblots and thus were not localised to the site of plaques, where greatest changes have been identified [84,85]. We similarly detected no changes in the expression levels for Iba1, a general marker of microglia.…”
Section: Neuro-inflammationmentioning
confidence: 82%